2014
DOI: 10.1093/europace/euu128
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplakin truncations and arrhythmogenic left ventricular cardiomyopathy: characterizing a phenotype

Abstract: DSP c.1339C>T is associated with an aggressive clinical phenotype of left-dominant arrhythmogenic cardiomyopathy and left ventricular non-compaction. Truncating mutations in desmoplakin are consistently associated with aggressive phenotypes and must be considered as a risk factor of sudden death. Since ventricular tachycardia occurs even in the absence of severe systolic dysfunction, an implantable cardioverter-defibrillator should be indicated promptly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 25 publications
8
67
1
4
Order By: Relevance
“…DP missense mutations can lead to Carvajal/Naxos syndrome, which is characterized by cardiomyopathy, palmoplantar keratoderma and wooly hair and is occasionally coupled with dental phenotypes (Chalabreysse et al 2011; Keller et al 2012). Recent genetic familial studies of arrhythmogenic cardiomyopathies have identified additional DP nonsense mutations that result in right- or left-dominant cardiomyopathies (Campuzano et al 2013; Lopez-Ayala et al 2014). Finally, a “hotspot” for arrhythmogenic cardiomyopathy mutations was identified within the N terminus of DP spanning residues 250–604 (Kapplinger et al 2011).…”
Section: Desmoplakinmentioning
confidence: 99%
“…DP missense mutations can lead to Carvajal/Naxos syndrome, which is characterized by cardiomyopathy, palmoplantar keratoderma and wooly hair and is occasionally coupled with dental phenotypes (Chalabreysse et al 2011; Keller et al 2012). Recent genetic familial studies of arrhythmogenic cardiomyopathies have identified additional DP nonsense mutations that result in right- or left-dominant cardiomyopathies (Campuzano et al 2013; Lopez-Ayala et al 2014). Finally, a “hotspot” for arrhythmogenic cardiomyopathy mutations was identified within the N terminus of DP spanning residues 250–604 (Kapplinger et al 2011).…”
Section: Desmoplakinmentioning
confidence: 99%
“…They postulated that different signaling pathways explain the different molecular signatures observed in LDAC and ARVC. 22 We extended these previous findings using novel IHC markers to characterize selected protein distribution in LV myocardial tissue. Junction plakoglobin signal intensity was depressed or absent at the intercalated disks in the majority (4/6; 67%) of our cases fulfilling ARVC criteria but signal intensity was normal at the intercalated disks in our two DCM cases, confirming the different molecular signatures of protein distribution patterns depending on the phenotype.…”
Section: Discussionmentioning
confidence: 78%
“…5 Junction plakoglobin redistribution thus seemed to track with phenotype rather than genotype. Interestingly, López-Ayala et al 22 also saw no junction plakoglobin redistribution in a similar LDAC phenotype caused by a desmoplakin truncating variant.…”
Section: Discussionmentioning
confidence: 95%
“…Dsg2 and Dsc2 are known to be expressed in cardiac myocytes and are the main candidate genes for this disorder (Pilichou et al, ; Syrris et al, ). ARVD/C was thought to primarily affect the right ventricle, however, in some cases the disease can affect the left ventricle ( Left dominant arrythmogenic cardiomyopathy ) and truncating mutations in desmoplakin are consistently associated with these aggressive phenotypes (López‐Ayala et al, ). – Woolly hair is a clinical feature shared syndromically with palmoplantar hyperkeratosis and heart anomalies by diseases such as: – Naxos disease , if Pg is targeted, which is an autosomal recessive, inherited, cardiocutaneous disorder, characterized by ARVC, woolly hair, and PPK. – Carvajal syndrome , if Dp is targeted, which is characterized by PPK, curly hair, dilated cardiomyopathy, especially on the left ventricle side, and early morbidity. – Ectodermal dysplasia–skin fragility syndrome (EDSFS) is an autosomal recessive dermatosis that has been associated with at least eleven different recessively inher­ited mutations in the Pkp1 gene. It is characterized by skin fragility (with trauma‐induced erosions and blistering), non‐cicatricial alope­cia, palmoplantar keratoderma (PPK), onichodystrophy, and in some cases hypohidrosis (McGrath et al, ; Hernández‐Martín et al, ). – Lethal acantholytic epidermolysis bullosa is a rare genetic disease that has also been identified as the result of heterozygosity of two loci containing the C terminus of Dsp and leading to the formation of a truncated protein, thus lacking the entire domain that binds the intermediate filaments.…”
Section: Desmosome Diseasesmentioning
confidence: 99%